Handbook of Vibrational Spectroscopy 2001
DOI: 10.1002/0470027320.s0609
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Cavity Ringdown Spectroscopy

Abstract: Coherent two‐dimensional vibrational spectroscopies use multiple laser excitations at high intensities where nonlinear processes dominate. These new spectroscopies can potentially probe molecular structure and dynamics in complex systems like multidimensional nuclear magnetic resonance (NMR) methods. We describe the development of the optical analogue to two‐dimensional NMR and its unique capabilities for achieving spectral selectivity. The approach uses four‐wave mixing where three las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…However, for CRDS, as equation 2 demonstrates, the ringdown time will incorporate absorption due to the concentration of both SO 2 and mercury. The PI and associates noted [20][21][22][23][24][25][26] in related research, that the presence of isotopic structure during a scan of the mercury 253 nm line raised the possibility (later, confirmed) that absorbance components of complex mixtures can be separated (Fig 4a). 27,28 For example, using a gas mixture containing 1.2 ppb mercury and 2175 ppm SO 2 respectively (Fig.…”
Section: Interferencesmentioning
confidence: 92%
See 4 more Smart Citations
“…However, for CRDS, as equation 2 demonstrates, the ringdown time will incorporate absorption due to the concentration of both SO 2 and mercury. The PI and associates noted [20][21][22][23][24][25][26] in related research, that the presence of isotopic structure during a scan of the mercury 253 nm line raised the possibility (later, confirmed) that absorbance components of complex mixtures can be separated (Fig 4a). 27,28 For example, using a gas mixture containing 1.2 ppb mercury and 2175 ppm SO 2 respectively (Fig.…”
Section: Interferencesmentioning
confidence: 92%
“…The PI and associates noted [20][21][22][23][24][25][26] in related research, that the presence of isotopic structure during a scan of the mercury 253 nm line raised the possibility (later, confirmed) that absorbance components of complex mixtures can be separated (Fig 4a). 27,28 For example, using a gas mixture containing 1.2 ppb mercury and 2175 ppm SO 2 respectively ( By utilizing the fine absorption structure it has been demonstrated that accurate determination of individual components, down into the ppt range, can be successfully achieved.…”
Section: Interferencesmentioning
confidence: 92%
See 3 more Smart Citations